Organizacja i funkcjonowanie Wyższego Seminarium Duchownego w Koszalinie w latach 1981–2011 - Apanel, Danuta (Biuletyn Historii Wychowania, 2012)
The study hereby proposed presents the activity of a Catholic college - Higher Theological Seminary in Koszalin in the years 1981-2011. The College came into being thanks to the efforts of Bishop Ignacy Jeż. In the abovementioned period, the college was administered by five rectors and seven administrative directors. There were 658 students (alumni) and 362 deacons, who took holy orders. During the six-year program of education, students learned the obligatory, pastoral and theological subjects as well as underwent practical training. The thesis defense took place in the fifth year of studies. The sixth year was intended for practicing and taking religious vows.